2015
DOI: 10.3390/ijms16048430
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Bio-Based Solvents for Extraction of Fat and Oils: Solubility Prediction, Global Yield, Extraction Kinetics, Chemical Composition and Cost of Manufacturing

Abstract: The present study was designed to evaluate the performance of alternative bio-based solvents, more especially 2-methyltetrahydrofuran, obtained from crop’s byproducts for the substitution of petroleum solvents such as hexane in the extraction of fat and oils for food (edible oil) and non-food (bio fuel) applications. First a solvent selection as well as an evaluation of the performance was made with Hansen Solubility Parameters and the COnductor-like Screening MOdel for Realistic Solvation (COSMO-RS) simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
92
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 152 publications
(99 citation statements)
references
References 16 publications
3
92
0
4
Order By: Relevance
“…Since the studied PILs are ethanol-and water-soluble along a wide range of compositions 3,35 , samples were cleaned with these solvents before the morphological characterization, with the removal of most of the PIL from the surface. For cleansing the commercial lubricant and given its nature of vegetable oil, the most appropriate is the removal with solvents like n-hexane or tetrahydrofuran 36 . Ethanol is not a good solvent for vegetable oils.…”
Section: Methodsmentioning
confidence: 99%
“…Since the studied PILs are ethanol-and water-soluble along a wide range of compositions 3,35 , samples were cleaned with these solvents before the morphological characterization, with the removal of most of the PIL from the surface. For cleansing the commercial lubricant and given its nature of vegetable oil, the most appropriate is the removal with solvents like n-hexane or tetrahydrofuran 36 . Ethanol is not a good solvent for vegetable oils.…”
Section: Methodsmentioning
confidence: 99%
“…205e219;Ishida & Chapman, 2009). As examples, studies have been performed regarding the extraction of rapeseed oils using MeTHF Sicaire, Vian, Fine, Joffre et al, 2015), caraway seeds aromas using a-pinene (Filly, Fabiano-Tixier, Fernandez, & Chemat, 2015) and extraction of rice bran oil using limonene (Mamidipally & Liu, 2004). Such solvents have a good solvation power, are non-toxic and biodegradable (Chemat, 2011, p. 9).…”
Section: Introductionmentioning
confidence: 99%
“…The value of the effective diffusion coefficient estimated by this fitting was D eff = (1.86 ± 0.02) Â 10 À11 m 2 /s. In comparison, Sicaire et al (2015b) found a diffusion coefficient of 0.34 Â 10 À11 m 2 /s for rapeseed flakes in a conventional hexane extraction process (for a temperature of 55°C). The value of the effective diffusion coefficient characterizes the extraction kinetics for a given temperature and solvent type independently of the particle size and solvent/solid ratio.…”
Section: Extraction Kineticsmentioning
confidence: 99%
“…In brief, the analysis was based on the presentation of the flakes-solvent mixture as a polydisperse suspension with a known particle size distribution, and application of Crank's equation for diffusion from a monodisperse suspension of spherical particles (Crank, 1975) to each class of particle size j. Only the first term of the complete Crank's diffusion equation was used (as it was previously done by Allaf et al (2014) and Sicaire et al (2015b)), since superior terms had only insignificant impact on the result of analysis at the studied extraction time range, t > 2 min. The total oil extraction yield Y t mod was calculated as a sum of the extraction yield from each particle class j:…”
Section: Analysis Of Extraction Kineticsmentioning
confidence: 99%
See 1 more Smart Citation